Position Optimization of SDVA Mass (1/20 System Mass) to Reduce Translation and Rotation Vibration on Beam - Susastro Suharto (Jurnal Teknik Mesin (JTM), 2017)
In many cases, amount of SDVA mass  (single dynamic vibration absorber) which is used to dampen vibrations is equal to 1/10 of the mass of the system. Meanwhile, the amount of additional mass is sometimes felt to be too great if the mass system  is also great. To resolve this  problem, we use mass absorber with a much smaller size. In this research, we did a simulation optimization of the use massa SDVA 1/20 on the beam, to damped translation and rotation vibration from main system. The study began by building a 2 DOF vibration prototype system with the addition of SDVA. Prototype modeled into mathematical equations and simulated to determine the change vibration characteristics. In this simulation we provide changes in the excitation frequency and distance of the center of mass SDVA future main system. From this research indicated that the addition of SDVA capable of reducing vibration direction of translation by 98.53% that occurred at a frequency ratio of 1. Whereas for rotational motion, vibration reduction which occurred amounted to 80.41%. From the results of This research also concluded that translation and rotation vibration reduction are best obtained when the ratio of the arms by rl = 0,9 with 75,84 % vibration reduction.